Comparative Morphology of the Papillae Linguales and their Connective Tissue Cores in the Tongue of the Greater Japanese Shrew‐mole, Urotrichus talpoides. (10th May 2012) - Yoshimura, K.; Shindo, J.; Kageyama, I.
Summary The external morphology of the papillae linguales (papillae filiformes, papillae fungiformes and papillae vallatae) and their connective tissue cores (CTCs) of the greater Japanese shrew‐mole (Urotrichus talpoides) were analysed by optical and scanning electron microscopy. Papillae filiformes were distributed over the dorsal surface of the apex linguae, and on the rostral and caudal regions of the corpus linguae but were less numerous in the mid‐region. They were absent from the radix linguae. A pair of oval papillae vallatae was situated at the border between the corpus linguae and the radix linguae. Papillae foliatae were absent. The epithelial surface of each papilla filiformis consisted of a circular concavity, a ring‐like wall and either a single thumb‐like process or 2–3 slender pointed processes, depending on their location. The morphology of the CTCs of the papillae filiformes also varied regionally. The papillae linguales of the Japanese shrew‐mole were morphologically similar to those of other Talpidae and Soricidae, including the common shrew, particularly with respect to the papillae filiformes in the mid‐ and caudal regions of the corpus linguae.